Antimicrobial polyketides and sesquiterpene lactones from the deep-sea cold-seep-derived fungus Talaromyces minioluteus CS-113 triggered by the histone deacetylase inhibitor SAHA. Issue 12 (7th March 2023) - Yang, Sui-Qun; Song, Qi; Li, Xiao-Ming; Li, Xin; Li, Hong-Lei; Meng, Ling-Hong; Wang, Bin-Gui
Abstract : First report of the chemical diversity study of deep-sea cold-seep-derived fungi triggered by the histone deacetylase inhibitor SAHA. Abstract : Seven new highly oxygenated natural products with diverse chemical structural types, including three new glucosidic polyketides, talaminiosides A–C (1–3 ), a pair of racemic aromatic polyketides, (±)-talaminone A (4a and 4b ), two new azaphilone polyketides, (+)-5-chloromitorubrinic acid (5 ) and 7- epi -purpurquinone C (7 ), and one new drimane sesquiterpene lactone, 11-hydroxyminioluteumide B (8 ), together with a pinazaphilone B sodium salt (6 ) and 10 known compounds (9–18 ), were isolated and identified from the culture extract of Talaromyces minioluteus CS-113, a fungus obtained from deep-sea cold-seep sediments collected from the South China Sea. LCMS results indicated that compounds 3 and 4 might be produced by the real activation of silent BGCs triggered by the histone deacetylase inhibitor SAHA, and some of the other compounds were enhanced minor components. Their structures were elucidated by the detailed interpretation of NMR spectroscopic and mass spectrometric data, X-ray crystallographic analysis, ECD and specific rotation (SR) calculations, and DP4+ probability analysis. Compound 7, an azaphilone derivative, exhibited potent activities against several agricultural pathogenic fungi with MIC values equivalent or comparable to amphotericin B. The structure–activity relationship of the isolated azaphilones is briefly discussed. This is the first report of the chemical diversity study of deep-sea cold-seep-derived fungi triggered by SAHA, providing a useful strategy for the activation of cryptic fungal metabolites from deep-sea-derived fungi.